Expression of BMI1 and p16 in laryngeal squamous cell carcinoma. Issue 6 (22nd June 2012) - Allegra, Eugenia; Caltabiano, Rosario; Amorosi, Andrea; Vasquez, Enrico; Garozzo, Aldo; Puzzo, Lidia
Abstract Background The clinical evolution of laryngeal squamous cell carcinoma (SCC) is undetectable with the current staging criteria. To more completely understand the biology of laryngeal SCC, we assessed the expression of the proteins B‐cell–specific Moloney murine leukemia virus integration site 1 (BMI1) and p16. Methods We assessed immunohistochemically the expression of BMI1 and p16 in 25 laryngeal SCCs at different stages. Results High BMI1 expression was detected in 11.7% of glottic tumors and in 50% of supraglottic tumors. No significant differences were observed in the patients' clinical data after they were stratified by the tumor expression of p16. The expression of nuclear BMI1 in the absence of p16 immunoreactivity correlated significantly with the pN status of the primary tumors. Conclusion Nuclear BMI1 expression in the absence of p16 expression seems to characterize a subset of patients with a high risk of developing lymph node metastasis. © 2012 Wiley Periodicals, Inc. Head Neck, 2012